Broadband Photoresponses from Ultraviolet to Near‐Infrared (II) Region through Light‐induced Pyroelectric Effects in a Hybrid Perovskite. (29th November 2022) - Guo, Wuqian; Xu, Haojie; Weng, Wen; Tang, Liwei; Ma, Yu; Liu, Yi; Hua, Lina; Wang, Beibei; Luo, Junhua; Sun, Zhihua
Abstract: Broadband photodetection has shown a great promise for diverse applications, while the realization of plateau photoresponse from ultraviolet (UV) to near‐infrared (NIR) spectral region is very challenging. Herein, we exploit photoexcited pyroelectric effect in a chiral hybrid perovskite, ( N, N ‐dimethylcyclohexylammonium)PbBr3 (1 ), serving as a new pathway to drive broadband photoactivities. It is a room‐temperature pyroelectric with large polarization of ≈6.4 μC cm −2 and high pyroelectric figure‐of‐merits ( F V =1.0×10 −2  cm 2   μC −1 and F D =7.1×10 −5  Pa −1/2 ). Strikingly, light‐induced pyroelectric effect arising from spontaneous polarization is observed in 1, which cover UV (266 nm) to NIR‐II (1950 nm) full spectral region. The broadband photoresponses actualized by pyroelectricity break the limit of optical band gap. As the first demonstration of photo‐pyroelectricity covering UV‐to‐NIR spectral region in hybrid perovskites, this work paves a pathway to assemble high‐performance smart devices. Abstract : We realize broadband photoresponses covering UV‐to‐NIR‐II (266–1950 nm) spectral region through light‐induced pyroelectric effect in a hybrid perovskite, which breaks the limitation of intrinsic optical band gap and provides a feasible way toward assembling broadband high‐performance devices.